(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
There is high consumption of oxygen cylinder valves due to incorrect application of valves, therefore, this research will study the possibility to modify Brass alloy that used to produce cylinder valves and reduce their erosion that happens under the use of valve. The main type of brass that used to make cylinder valve is CW713R which contained aluminum with percentage of 1.3-2.3% with hardness of 174 HV. Therefore, the effect of aluminum element on the properties of brass alloy will study to find the best and the optimum percentages that can be added to improve the hardness and machinability of cylinder valve. Brass scrap was melted using oil fire furnace and aluminum element was added before it cast. Then, the melting liquid was poured on steel die casting mold. The result shows that the hardness Brass cylinder valve was increased by increasing the percentage of aluminum element. It is raised from 206 to 605 HV. But when the percentage of aluminum reached 10 % the Brass material becomes brittle and difficult to machine. The best percentage of aluminum that can be added to brass alloy lies in the range of 2.5 – 5%.